Identifikasi Titik Api Lilin Berbasis Nilai HSV , Threshold dan Momen Citra untuk Aplikasi Robot Pemadam Api - Wiyagi, Rama Okta; Soesanti, Indah; Susanto, Adhi (Jurnal Semesta Teknika, 2014)
Fire fighting robot is robot that has function to find and extinguish a candle flame in the space arena. To be able carry out their duties then the robot is equipped with sensors, controllers and drivers. Phototransistor, thermopile arrays, or UVTron is sensors that usually used in fire fighting robot. These sensors have some drawbacks. Phototransistor has a relatively close distance readings. While TPA81 thermopile array has a narrow field of reading only 41 Â° x 6 Â° from sensor. UVtron only limited to determine whether there is any point of the fire and was unable to determine absolute position or angle of the hotspots and vulnerable to damage if the jar is touched by the hand. Additionally TPA81 sensors and sensor UVtron is relatively expensive. This research aims to build a candle light detection alternative better in terms of specification, performance, price, reliability and ease of development. As the input of the system identification using webcams camera types. The webcam running on Raspberry Pi single-board computer. Image information is converted to HSV color space (Hue, Saturation, Value) and applied threshold processing. Thresholding HSV performed on the range of values contained in the object candle flame. To get the absolute position of a candle flame using moments analysis. Identification system can identify candle flame spot with the farthest distance is 225cm. Angle readings in the horizontal plane by 60 Ë and the vertical plane by 40 Ë. The achievement of the highest FPS obtained in image resolution size of 320 x 240 pixels which is 8.129 FPS.